ENVIRONMENTAL LICENSING IN COMPARATIVE PERSPECTIVE: LESSONS FROM SPAIN, FRANCE, PORTUGAL AND THE UNITED STATES - de Giorge Cerqueira, Homero (Revista Gênero e Interdisciplinaridade, 2025)
This article analyzes environmental licensing as an essential instrument for environmental protection, comparing the models adopted in Spain, France, Portugal and the United States. The research, using a comparative approach, evaluates the practices and legislation of these countries, identifying good practices and challenges. It is concluded that the effectiveness of licensing depends on adaptation to local specificities and the ability to balance environmental protection and economic development. This study provides support for improving regulatory systems in different contexts.